Fabrication of electrospun keratin nanofiber membranes for air and water treatment. Issue 7 (31st May 2019) - Figoli, Alberto; Ursino, Claudia; Sanchez Ramirez, Diego Omar; Carletto, Riccardo Andrea; Tonetti, Cinzia; Varesano, Alessio; De Santo, Maria Penelope; Cassano, Alfredo; Vineis, Claudia
Abstract : Keratin proteins extracted from wool fibers by sulfitolysis were electrospun for the production of active nanofiber membranes (NFMs). The keratin NFMs were composited with nylon woven fabric for improving their mechanical properties as a filtration material. The prepared membranes were characterized in terms of morphology, pore size, contact angle, and performance of water and air permeability. Experimental data showed that most of investigated parameters were affected by the electrospinning time: that is, roughness rose by increasing the electrospinning time, while the narrowest pore size distribution was obtained at the longest electrospinning time (2 h). The pure water permeability ( PWP ) was greater for the produced NFMs than for the commercial microfiltration membranes and decreased by increasing the electrospinning time. At the longest electrospinning time, the produced NFMs showed a PWP of about 45.7 m 3 /m 2 h bar, which is a value greater than those obtained by conventional materials used in water filtration, including microfiltration membranes. According to the data of contact angle measurements, the high hydrophobicity of NFMs membranes could reinforce their stability in water. Other potential applications could be venting, adsorption of VOCs, and separation of oils from oil/water emulsions. POLYM. ENG. SCI., 59:1472–1478 2019. © 2019 Society of Plastics Engineers